Madam de Bedamore Through the Keyhole: Scandal, Local Knowledge, and Things Unpublished in Late-Stuart England. (2nd January 2021) - Key, Newton
ABSTRACT: What happened after Barbara Coningsby discovered Thomas Coningsby alone with Lady Frances Scudamore upset individual lives, families, and Herefordshire political alliances in 1681 and 1682. It also became the subject both of scandalous gossip across England and of Bishop Herbert Croft's year-long attempt to have Lady Scudamore do penance. Later, the story resurfaced in Delarivier Manley's satirical New Atalantis (1709). Comparing rumour-filled correspondence with printed satire suggests that historians' approaches to early modern scandal – prosopographical, rhetorical, legal institutional, or psycho-social – need to be revised or expanded to include the circulation of 'things unpublished'. Because innuendo and allusions in both correspondence and printed satire obscure as much as they reveal, contemporaries relied on local knowledge to plumb levels of meaning. And academics can use such local knowledge to decipher the levels of significance of early modern scandal.